Effect of Swirl Number on the Combustion Characteristic of Syngas using FGM Model Simulation - Samiran, N.; N. M. Jaafar, M.; T. Chong, C.; N. M. Hassan, N.; L. M. Tobi, A. (International Journal of Engineering and Technology, 2019)
Synthesis gas (syngas) is one of the potential alternative clean fuel energy in gas-fired boilers swirl burners system. Computational Fluid Dynamic (CFD) simulations were conducted to study the effect of different swirl number on the combustion characteristics of CO-rich syngas in premixed swirl mode using a model boiler swirl burner. The composition of CO-rich syngas is 67.5 % CO, 22.5 % H2, 5 % CO2 and 5 % CH4. Two types of combustion model for simulation analysis were used in this study namely flamelet generated manifold (FGM) and chemical equilibrium (CE) approaches. The CFD results were validated with actual experimental data with the same swirl number. The FGM method shows better agreement with experimental result, hence adopted to model and predict the CO-rich syngas flame characteristic in the reaction zones. The CO-rich syngas was then numerically tested on different type of swirl number including 0.39, 0.59, 0.84, 1.20 and 1.80. Result shows that the angle of flame distribution was apparently equivalence with the vane angle swirler. Swirler with a higher swirl number (1.20 and 1.80) showed lower NO (57%) and lower CO (98%) species compared to the one with a lower swirler number (0.39 â€“ 0.84). Flame with lower swirl number (0.39) exhibited higher temperature, OH and O radical content. Thus, it contribute to the high production of NO and CO species.Â Â